2010
DOI: 10.1063/1.3457390
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoelectric and magnetoelastic properties of rare-earth ferroborates

Abstract: The magnetic, electric, magnetoelectric, and magnetoelastic properties of rare-earth ferroborates RFe3(BO3)4 (R=Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er) as well as yttrium ferroborate YFe3(BO3)4 have been studied comprehensively. A strong dependence not only of the magnetic but also magnetoelectric properties on the type of rare-earth ion, specifically, on its anisotropy, which determines the magnetic structure and the large contribution to the electric polarization, has been found. This is manifested in the strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
110
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 168 publications
(138 citation statements)
references
References 28 publications
10
110
0
6
Order By: Relevance
“…Investigation of magnetic and magnetoelectric properties of the HoFe 3 (BO 3 ) 4 single crystal showed that it also refers to multiferroics [4][5][6]. In this crystal the considerable electric polarization in magnetic field [6], the giant magnetodielectric effect and the spontaneous polarization in the region of magnetic ordering [4] were found.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Investigation of magnetic and magnetoelectric properties of the HoFe 3 (BO 3 ) 4 single crystal showed that it also refers to multiferroics [4][5][6]. In this crystal the considerable electric polarization in magnetic field [6], the giant magnetodielectric effect and the spontaneous polarization in the region of magnetic ordering [4] were found.…”
Section: Introductionmentioning
confidence: 95%
“…Number and polarizations of lines in this band correspond to the splitting in the D 3 symmetry according to (5), (10) (Fig. 11).…”
Section: Transitionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 However, recent observations of improper ferroelectricity, 4,5 anomalous even within the realm of magnetoelectricity, require an even better understanding of the subject. Rare earth iron borates RFe 3 (BO 3 ) 4 , where R = rare earth, [6][7][8][9] are multiferroics, characterized by long-range magnetic wave vectors q c*, [10][11][12][13][14][15] and show a large magnetoelectric effect ( P ∼ 100 μC m −2 ). The RFe 3 (BO 3 ) 4 crystal structure 16,17 allows a dominant Fe-Fe exchange interaction, which is reflected by a T N in a narrow temperature range (30-40 K) for compounds with different R. The rare earth exchange interaction takes place via O and B, i.e., R-O-B-O-R.…”
Section: Introductionmentioning
confidence: 99%
“…Rare-earth iron-borates represent one exotic class of multiferroics [46][47][48]. At high temperatures, all rareearth borates reveal a non-centrosymmetric trigonal structure belonging to the space group R32 [49][50][51][52] which persist down to lowest temperatures for Sm-and Nd-ironborates [53].…”
mentioning
confidence: 99%